AKTIVITAS KAUM PEREMPUAN DALAM BIDANG POLITIK (Kajian Pemikiran Abu Al-A’lâ Al-Maudûdî) - Tri Masulah (MUWAZAH : jurnal kajian gender, 2009)
Politics is a gray area does not know which is right and falsehood. In the political world is not the technical term is “wrong” all the steps that must be “right” and “systematic” does not care whether the way is used hurt or benefit others. In the political world does not know friend or foe whom is eternally eternal interests. In this paper, Abu Ala Maududi is as one of fundamentalist leaders to write his thoughts on women in pakistan political activities that are not consistent in Mawdudi’s view. Maududi never support a woman become president by supporting the candidacy of Fatimah Ali Jinnah became President of Pakistan, and on the other hand he states that women should only work in the domestic sector where she should not be working in the public sector, including the President and Parliament. This shows that the political purpose for anyone, including the interests of fundamentalist Mawdudi.